the effect of Guillard fertilizer treatment on the growth of the diatom skeletonema costatum in bpbap batee tip - Nursantika Adelia Putri; Nabila Ukhty; Afdhal Fuadi; Supartik Supartik (Jurnal Fish Protech, 2023)
This study aims to determine the growth phase of Skeletonema costatum with different concentrations of Guillard fertilizer and to determine the effect of Guillard fertilizer concentration on the quality of the growth medium for Skeletonema costatum.  This study used an experimental research method with 4 stages of research, namely preparation of Guillard fertilizer, preparation of aqueous media, preparation of Skeletonema costatum culture and observation of the growth phase.  Data from testing the parameters for measuring water quality were analyzed descriptively.  The design used in this study was RAL with 4 treatments, namely without guillard fertilizer (NP0), BPBAP dose of guillard fertilizer (NP1), increased dose of guillard fertilizer (NP2), and reduced dose of guillard fertilizer (NP3) with 4 repetitions.  test.  The results showed that the doses of NP0, NP2 and NP3 had less optimal growth compared to the NP1 dose where the density was optimal according to SNI 4958:2015.  The average pH quality is 7-9, the average DO quality is 3-7, the average salinity quality is 29-35 ppt, the average temperature quality is 20-30ºC and the average light quality is 500-1200 lux.Keywords: Skeletonema costatum, Guillard, Growth, Water Quality Parameters